The BCL-2 inhibitor ABT-199/venetoclax synergizes with proteasome inhibition via transactivation of the MCL-1 antagonist NOXA - Sandra Weller; Astrid Toennießen; Benjamin Schaefer; Tobias Beigl; Alina Muenchow; Kathrin Böpple; Ute Hofmann; Bernhard F. Gillissen; Walter E. Aulitzky; Hans-Georg Kopp; Frank Essmann (Cell Death Discovery, 2022)
Abstract Enhanced expression of anti-apoptotic B-cell lymphoma 2 (BCL-2) protein is frequent in cancer. Targeting of BCL-2 with the specific inhibitor ABT-199 (Venetoclax) has significant clinical activity in malignant diseases such as chronic lymphocytic leukemia and multiple myeloma. The small molecule drug ABT-199 mimics the pro-apoptotic BCL-2 homology domain 3 of BH3-only proteins and blocks the hydrophobic BC-groove in BCL-2. We have previously shown that ABT-199 synergizes with the proteasome inhibitor (PI) bortezomib in soft tissue sarcoma derived cells and cell lines to induce apoptosis. Synergistic apoptosis induction relies on the pore-forming effector BAX and expression of the pro-apoptotic BH3-only protein NOXA. Bortezomib augments expression of NOXA by blocking its proteasomal degradation. Interestingly, shown here for the first time, expression of NOXA is strongly enhanced by ABT-199 induced integrated stress response (ISR). ISR transcription factors ATF3 & ATF4 mediate transactivation of the BH3-only protein NOXA which specifically inhibits the anti-apoptotic MCL-1. Thus, NOXA potentiates the efficacy of the BCL-2 inhibitor ABT-199 by simultaneous inhibition of MCL-1. Hence, ABT-199 has a double impact by directly blocking anti-apoptotic BCL-2 and inhibiting MCL-1 via transactivated NOXA. By preventing degradation of NOXA PIs synergize with ABT-199. Synergism of ABT-199 and PIs therefore occurs on several, previously unexpected levels. This finding should prompt clinical evaluation of combinatorial regimens in further malignancies.